2004
DOI: 10.1080/0929821042000317822
|View full text |Cite
|
Sign up to set email alerts
|

Which Emotions Can be Induced by Music? What Are the Underlying Mechanisms? And How Can We Measure Them?

Abstract: The study of emotional effects of music is handicapped by a lack of appropriate research paradigms and methods, due to a dearth of conceptual-theoretical analyses of the process underlying emotion production via music. It is shown that none of the three major assessment methods for emotion induction -lists of basic emotions, valence-arousal dimensions, and eclectic emotion inventories -is well suited to the task. By focusing on a small number of evolutionarily continuous basic emotions one downplays the more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
322
3
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(351 citation statements)
references
References 35 publications
7
322
3
8
Order By: Relevance
“…Three findings support this interpretation. First, sad music evoked, in addition to sadness, a range of positively toned, aesthetic emotions (see e.g., Scherer, 2004;Zentner et al, 2008). Second, those most able to appreciate aesthetic experiences and beauty -those highest in the trait Openness to Experience -most liked sad music.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three findings support this interpretation. First, sad music evoked, in addition to sadness, a range of positively toned, aesthetic emotions (see e.g., Scherer, 2004;Zentner et al, 2008). Second, those most able to appreciate aesthetic experiences and beauty -those highest in the trait Openness to Experience -most liked sad music.…”
Section: Discussionmentioning
confidence: 99%
“…If sad music indeed evokes complex, aesthetic emotions (see e.g., Scherer, 2004), such experiences may be especially appealing to individuals with certain personalities. The trait Openness to Experience is related to a sensitivity to art and beauty (McCrae & Sutin, 2009), to a preference for diverse and complex music styles (e.g., Rentfrow & Gosling, 2003), and to the experience of aesthetic chills in response to music (Nusbaum & Silvia, 2011).…”
mentioning
confidence: 99%
“…Listeners' experience of emotions may be more subjective and socially dependent than their perception of emotion (see for discussions Gabrielsson, 2001Gabrielsson, /2002Scherer, 2004;Scherer & Zentner, 2001).Previous research has shown that listeners are quite consistent in labeling music with an emotional quality, especially where it concerns basic emotions (Gabrielsson & Juslin, 2003). This research has started to distinguish relevant musical features that are responsible for labeling music with a specific emotional category.…”
Section: Emotional Ornamentation In Performances Of a Handel Sonatamentioning
confidence: 99%
“…However, in this study, as in many others, participants were asked to recognize the emotions conveyed by the music, but not to assess their emotional experience when listening to the music. In the psychology of emotions and music psychology, a distinction is made between the recognition of emotions and the actual experience of emotions (Gabrielson and Juslin, 2003;Scherer, 2004). The recognition is viewed mainly as a cognitive process of assigning a label to an emotion expressed by the music.…”
Section: Introductionmentioning
confidence: 99%